2017
DOI: 10.1109/tns.2016.2615719
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Ion Irradiation Fluence Dependence for Single-Event Upsets in a NAND Flash Memory

Abstract: NAND Flash memories are currently the dominant mass storage technology in the commercial market, and they are finding their way into space systems thanks to the technology's high density and low cost [1]. NASA and other government agencies as well as academia have actively investigated the radiation susceptibility of each generation of NAND flash from various commercial vendors, including the Micron and Samsung [2]−[4]. The growing complexity of the device's control circuits as well as the continued shrinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…In a previous study, we found that the Micron 128 Gb planar NAND exhibited an inverse fluence dependence for the SEU cross section [20], where the cross section decreased with increasing fluence. We believed that the phenomenon is possible for any high-density device with a variable upset threshold distribution.…”
Section: Fluence Dependencementioning
confidence: 82%
See 4 more Smart Citations
“…In a previous study, we found that the Micron 128 Gb planar NAND exhibited an inverse fluence dependence for the SEU cross section [20], where the cross section decreased with increasing fluence. We believed that the phenomenon is possible for any high-density device with a variable upset threshold distribution.…”
Section: Fluence Dependencementioning
confidence: 82%
“…The authors alluded to the introduction of devices with multiple storage levels in the future, which they speculated could introduce further complexity to the radiation response. In fact, more recent studies have shown that SEU susceptibility can be substantial in multiple-level cell (MLC) or triple-level cell (TLC) devices [18], [20]. The results illustrate how the technological progress can impact radiation effects.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations